2010
DOI: 10.1186/1478-7547-8-7
|View full text |Cite
|
Sign up to set email alerts
|

A health economic model for evaluating a vaccine for the prevention of herpes zoster and post-herpetic neuralgia in the UK

Abstract: BackgroundA live-attenuated vaccine aimed at preventing herpes zoster (HZ) and its main complication, post-herpetic neuralgia (PHN) is available in Europe for immunocompetent adults aged 50 years and more. The study objective is to assess the cost effectiveness of a vaccination program for this population in the UK.MethodsA state-transition Markov model has been developed to simulate the natural history of HZ and PHN and to estimate the lifetime effects of vaccination in the UK. Several health states are defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 24 publications
0
70
0
1
Order By: Relevance
“…32,33 Finally 14 cost-effectiveness studies of HZ vaccination remained and were systematically reviewed. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Main study characteristics Table 1 summarizes the main characteristics of the included studies ordered by publication date. Several studies did not mention all the main features reported in Table 1, such as time horizon, costing year, sensitivity analysis and funding.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…32,33 Finally 14 cost-effectiveness studies of HZ vaccination remained and were systematically reviewed. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Main study characteristics Table 1 summarizes the main characteristics of the included studies ordered by publication date. Several studies did not mention all the main features reported in Table 1, such as time horizon, costing year, sensitivity analysis and funding.…”
Section: Study Selectionmentioning
confidence: 99%
“…Country and funding Of the 14 studies included, 9 were conducted in European countries (UK, Belgium, The Netherlands, Switzerland and France) [34][35][36][37][38][39][40][41][42][43][44][45][46][47] and 5 in non-European countries (US and Canada). [35][36][37][38][39] Six studies were funded by the pharmaceutical industry, 36,38,41,42,44,46 five studies by public resources 34,37,39,40,43,45 and two studies were performed without external funding.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations